A STUDY TO DERIVE BARRIERS OF PHYSICAL ACTIVITY AMONG ADULTS OF TERTIARY CARE TEACHING HOSPITAL OF CENTRAL INDIA - Sharma, Arun; Verma, Prashant; Thakur, Aditya; Tiwari, Rajesh (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The aim of the study was to derive the barriers of physical activity among the adults of tertiary care teaching hospital. Methods: It was descriptive and cross-sectional study carried out in the tertiary care teaching institute of Central India. The study was conducted during the period from January 2020 to October 2021. Study subjects were Participants belonging to 18–65 years age group studying or working at tertiary care teaching institute. Results: The proportion of insufficient physical among the participants was 8.62% while majority of the them, that is, 82.18% had moderate physical activity, whereas 9.2% of the respondents had vigorous physical activity. One hundred and sixteen (33.33%) had shown any of the perceived barriers to physical activity. Twenty (66.67%) in insufficiently active and 96 (33.57%) in moderately active group have shown any of the perceived barrier. Conclusion: As the long-term consequences of physical inactivity can lead to health problems among people, understanding the factors that influence participation in physical activity and barriers that leads to inactivity is important to help design successful interventions and strategies that increase their level of engagement in activity.